Operational risk in banks – revolution or regulatory evolution - Koleśnik, Jan (Research Papers of Wrocław University of Economics, 2018)
The aim of the article is to compare the methods of calculating capital requirement for operational risk in the banks with the new approach announced by the Basel Committee in December 2017. The analysis also demonstrated that the new rules are a genuine revolution in the field of comparability of capital requirements between all banks and evolution in the methodology of its calculation. Introduction of a single method of calculation of capital requirements for all banks instead of four methods and five variants of their combination applied so far will provide real comparability of capital requirements between banks for all stockholders. Considerable discretion of bank supervision, which allowed for unfounded interference with the method used by the bank, will also be eliminated. What is important, the new method – as compared to most of the methods used so far – will take into account data reflecting real bank exposure to operational losses
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 509, s. 168-178
Keywords: banks; operational risk; Basel Committee; capital requirements; banki; ryzyko operacyjne; Komitet Bazylejski; wymogi kapitałowe